Age-Specific Distribution of Diagnosis and Outcomes of Children Admitted to ICUs: A Population-Based Cohort Study*. Issue 7 (July 2019) - Jung, Minyoung; Park, Hyejeong; Kang, Danbee; Park, Jinkyeong; Jeon, Kyeongman; Chung, Chi Ryang; Yang, Jeong Hoon; Cho, Yang Hyun; Suh, Gee Young; Guallar, Eliseo; Cho, Juhee; Cho, Joongbum
Abstract : Objectives: Although several studies have reported outcome data on critically ill children, detailed reports by age are not available. We aimed to evaluate the age-specific estimates of trends in causes of diagnosis, procedures, and outcomes of pediatric admissions to ICUs in a national representative sample. Design: A population-based retrospective cohort study. Setting: Three hundred forty-four hospitals in South Korea. Patients: All pediatric admissions to ICUs in Korea from August 1, 2009, to September 30, 2014, were covered by the Korean National Health Insurance Corporation, with virtually complete coverage of the pediatric population in Korea. Patients less than 18 years with at least one ICUs admission between August 1, 2009, and September 30, 2014. We excluded neonatal admissions (< 28 days), neonatal ICUs, and admissions for health status other than a disease or injury. The final sample size was 38, 684 admissions from 32, 443 pediatric patients. Intervention: None. Measurements and Main Results: The overall age-standardized admission rate for pediatric patients was 75.9 admissions per 100, 000 person-years. The most common primary diagnosis of admissions was congenital malformation (10, 897 admissions, 28.2%), with marked differences by age at admission (5, 712 admissions [54.8%] in infants, 3, 994 admissions [24.6%] in children, and 1, 191 admissions [9.9%] in adolescents). Injury was the most common primary diagnosis in adolescents (3, 248 admissions, 27.1%). The overall in-hospital mortality was 2, 234 (5.8%) with relatively minor variations across age. Neoplasms and circulatory and neurologic diseases had both high frequency of admissions and high in-hospital mortality. Conclusions: Admission patterns, diagnosis, management, and outcomes of pediatric patients admitted to ICUs varied by age groups. Strategies to improve critical care qualities of pediatric patients need to be based on the differences of age and may need to be targeted at specific age groups. Abstract : Supplemental Digital Content is available in the text.